Key controls on the seasonal and interannual variations of the carbonate system and air‐sea CO2 flux in the Northeast Atlantic (Bay of Biscay). Issue 2 (13th February 2013) - Jiang, Zong‐Pei; Hydes, David J.; Tyrrell, Toby; Hartman, Sue E.; Hartman, Mark C.; Dumousseaud, Cynthia; Padin, Xose Antonio; Skjelvan, Ingunn; González‐Pola, César
Abstract: [1] Biogeochemical variations of surface water in the Northeast Atlantic (Bay of Biscay) were examined using high‐frequency underway measurements combined with monthly sampling of carbon‐related variables. The mechanisms controlling seasonal CO2 variability were investigated by distinguishing the contributions of biological and physical processes to the monthly changes in dissolved inorganic carbon (DIC) and partial pressure of CO2 ( p CO2 ). The seasonality of DIC (47–81 µmol kg −1 ) had a single peak with a winter maximum primarily driven by vertical mixing and a summer minimum driven by spring biological removal. Non‐Redfield C:N uptake was observed in the nutrient‐depleted summer but not during the spring bloom. In the North Atlantic, p CO2 seasonality shows a latitudinal transition: from the temperature‐dominated oligotrophic subtropical gyre to the subpolar region where p CO2 is dominated by changing concentrations of DIC. In the midlatitude Bay of Biscay, the annual cycle of p CO2 (61–75 µatm) showed a double‐peak distribution. The summer p CO2 peak was mainly driven by temperature increase, while the winter peak resulted from the dominant effect of entrainment of subsurface water. Interannual variations of DIC were more pronounced in winter and were driven by the changes in the strength of winter mixing. Higher wintertime concentrations and seasonal amplitudes of DIC were observed in cold years when the mixed‐layer depths were deeper, which appears to be associated with negative phases of the North Atlantic Oscillation. The Bay of Biscay shows a decrease of CO2 uptake in 2008–2010 (−0.97 and −0.75 mol m −2  yr −1 ) compared to 2002–2004 (−1.47 and −1.68 mol m −2  yr −1 ). Key Points: double‐peak pCO2 annual cycle in the Northeast Atlantic interannual variations of DIC relating to winter mixing and the NAO decreasing CO2 uptake in the Northeast Atlantic from 2002 to 2010